Identification of a cosmid clone containing the Neurospora crassa lys-5 and un-4 genes, isolation of a partial lys-5 cDNA and associated chromosome walking. - Thomas J Schmidhauser; Dan Chen; Yihong Wan (Fungal Genetics Reports, 1999)
The un-4 gene of Neurospora crassa was cloned to determine the limits of a chromosome walk on linkage group VI (LGVI) and to allow analysis of un loci on LGVI. Subsequent analysis identified the lys-5 locus on the same cosmid clone as un-4. We have isolated and sequenced a partial lys-5 cDNA clone and initiated a chromosome walk from the lys-5, un-4 cosmid clone.